His own where - Jordan, June, 1936-2002.; ebrary, Inc. (New York : Feminist Press, 2010)
With their lives spinning out of control, sixteen-year-old Buddy Rivers and his girl friend Angela create their own way of staying alive in Brooklyn in the mid-1960s.
Introduction by Sapphire.
Text copyright 1971 by June Jordan.
Electronic reproduction.
Keywords: African Americans -- Fiction; Love stories; Brooklyn (New York, N.Y.) -- History -- 20th century -- Fiction; Electronic books